Nanomolar phosphate supply and its recycling drive net community production in the subtropical North Pacific - Fuminori Hashihama (Nature Portfolio, 2021)
Primary productivity in the oligotrophic ocean sustains Earth’s ecosystems, but nutrient concentrations are vanishingly low. Here the authors measure nanomolar macronutrient concentrations in the North Pacific and find that net community production is sustained through high rates of phosphorus recycling.